2005
DOI: 10.1080/15602210500288852
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of the general level framework: Results of the South of England competency study†

Abstract: Background: Inconsistency in the practice of clinical pharmacy at a junior level encouraged our group to develop a general level competency framework (GLF) to facilitate practitioner development and assessment. The framework consists of patientrelated, personal and problem-solving clusters of competencies assessed on a four-point frequency scale. This study describes a large, controlled study to determine whether the framework could improve the clinical practice of junior hospital pharmacists.Method: One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 5 publications
6
76
0
Order By: Relevance
“…27 The present study demonstrated significant improvements in all competencies evaluated. This finding supports other studies that used the GLF to assess competencies, 12,23 though the results presented here show even greater improvement in pharmacist competencies. Coombes and colleagues demonstrated improvements in 57% of the competencies evaluated (35 of 61), and none of the remaining competencies demonstrated a decrease in performance between evaluations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…27 The present study demonstrated significant improvements in all competencies evaluated. This finding supports other studies that used the GLF to assess competencies, 12,23 though the results presented here show even greater improvement in pharmacist competencies. Coombes and colleagues demonstrated improvements in 57% of the competencies evaluated (35 of 61), and none of the remaining competencies demonstrated a decrease in performance between evaluations.…”
Section: Discussionsupporting
confidence: 92%
“…23 The South of England competency study was designed as a controlled study, and demonstrated that junior pharmacist competencies developed using the Framework improved in 24 of 25 areas assessed at 6 months and that this improvement was sustained at 12 months. 12 In both the above studies, the sample consisted of hospital/clinical pharmacists. Therefore, the greater improvement in competencies found in this study may have been due to the use of the GLF to evaluate community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The GLF allows accurate determination of a precise described meanings and level of such competencies. 10,11,15 There is a strong connection between competency and performance. Multiple-choice tests, oral examinations, or essays can be used to test factual knowledge, but more sophisticated methods are needed to assess performance, including observation, objective structured clinical examinations, and role play using standardized or real patients.…”
Section: General Level Framework (Glf)mentioning
confidence: 99%
“…10 GLF studies of postgraduate students and pharmacists employed in hospital pharmacies have been conducted in Great Britain and Australia. 11,12 Research studies also have been conducted of pharmacists delivering pharmaceutical care in community pharmacies in Great Britain. 13 The extrapolation of discovered patterns in community pharmacies in Croatia as a new field of investigation is presented in this study.…”
Section: Introductionmentioning
confidence: 99%